Landform approach for mining site evaluation in Galur sub district, Kulon Progo Regency, Yogyakarta Special Province - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2004)
The objectives of the study are (a) to determine the potency and characteristics of mineral deposits (b) to evaluate the land suitability for mining purposes based on landform unit approach in the Galur Sub district Kulon Progo Regency, Yogyakarta Special Province. Landform classification and mapping have been done using aerial photo interpretation. The landform units were used as sample areas to determine the mineral characteristics and the landform description. The characteristics of the minerals include physical characteristics such as grain size and chemicals composition. Stratified random sampling is used in the selection ofsand samples. Sand deposit is calculated by the extent of area x thickness x specific weight. The volcanic sands in the study area are potentially suitable for mining exploitation especially in the river terraces and river sand bar. Clay loam soils in the natural levee and alluvial plain are moderately potential, while sand deposit along the sand dunes are not suitable site for mining exploitation.